Intention to Engage in Winter Sport in Climate Change Affected Environments - Frühauf, Anika; Niedermeier, Martin; Kopp, Martin (Frontiers in Public Health, 2020)
Exercise, including winter sport activities, shows positive effects on physical and mental health, with additional benefits when participating in natural environments. Winter sport activities are particularly vulnerable to climate change, since global warming will decrease the duration and amount of snow. In the context of climate change in alpine environments, little is known on the determinants of winter sport behavior. Thus, the following study primarily aimed at comparing the effect of being exposed to a climate change affected scenario (CCA) or to a climate change unaffected scenario (CCU) on the intention to engage in recreational winter sport activities. Secondly, we aimed to analyze the role of anticipated affective responses during exercising based on the Theory of Planned Behavior (TPB). An experimental cross-sectional web-based study design was used. Participants were randomly allocated to pictures of either CCA or CCU. TPB variables and affective responses with regard to the displayed scenarios were assessed. Statistical analyses included Mann-Whitney-U Tests, linear regression, and mediation analyses. Significant group differences were seen in all TPB variables, p < 0.038; −0.13 < r < −0.30, as well as in affective responses, p < 0.001; −0.24 < r < −0.85. Lower intention to engage in winter sport activities and lower anticipated affective valence during exercising was found in CCA compared to CCU. Attitude toward winter sport was significantly positively associated with intention to engage in winter sport, beta = 0.66, p < 0.001. The effect of group allocation on attitude was mediated by anticipated affective valence, indirect effect = 0.37, p < 0.001. Intention to engage in recreational winter sport activities was lower in participants exposed to the climate change affected winter sport scenario. Since affective valence seems to influence attitude and consequently intention to exercise, the role of non-cognitive variables with regard to climate change related exposure should be considered in future studies. Therefore, winter sport resorts may consider altered winter sport behaviors due to the consequences of climate change as well as the importance of providing an optimal framework to enhance affective valence of their guests in order to mitigate potential changes in winter sports behavior.